Psychological Well-Being Assessed from Social Support in the Management of Teenagers of Orphanage Jamiyatul Al-Wasliyah Medan - Muhammad Hatta Wijaya; Catherine Meidany; Jessica Cendana; Sri Hartini (Journal of Business, Management, & Accounting, 2020)
High psychological well-being, occurs because adolescents at the Jamiyatul Al Wasliyah Orphanage Medan received high social support. Social support is both a perception and a situation where a person feels recognized, trusted, comfortable, cared for, valued, loved, and cared for. valued, loved, and cared for. This research aims to find the relationship between social support and Psychological well-being in adolescents in orphanages. The subjects used in this study were teenagers in the Jamiyatul Al Wasliyah Orphanage Medan. The results of the multiple regression test were R = 0,364 and the determination of coefficient was 0,132. This shows that 13,2% contribution of social support affects Psychological well-being